Organoleptic Test of Peanut-Based Cheese with Variations of Pineapple Skin and Coarse as Coagulants - Luhsarandini, Bivannie; Putri, Vairus Akmala; Anjely, Riska (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2025)
Background: Cheese is generally made from animal milk using rennet enzyme as a coagulant. However, consuming animal cheese carries the risk of increasing cholesterol due to its high saturated fat content. In addition, not everyone can consume animal protein due to allergies. Purpose: This study aims to develop a plant-based cheese product based on peanut milk by utilizing pineapple peel and stem as a natural coagulant. Method: The study design used a non-factorial completely randomized design (CRD) with four formulations: K1 (500 mL peanut milk: 500 mL pineapple peel-stem extract), K2 (500:450 mL), K3 (500:400 mL), and K4 (500:350 mL), each repeated three times. Observed variables included organoleptic properties (color, aroma, taste, texture). Organoleptic assessment by semi-trained panelists showed that formulation K1 had the highest scores for color (3.50), aroma (2.67), and texture (3.11), while K3 had the highest taste attribute with a score of 3.03. Result: The results of the ANOVA analysis for the organoleptic tests of color, aroma, taste, and texture show a p-value > 0.05, indicating no significant difference among the treatments applied. This study demonstrates that pineapple peel and core can be used as effective natural coagulants in the production of plant-based cheese made from peanut milk.